Effectiveness of Handheld Fan as A Non-Pharmacological Therapy in Reducing Dyspnea: A Scoping Review - Sandra Aprilia Putri; Ricky Putra Liyan; Nabilla Ramadhani; Gaviota Khalish; Chairul Huda; Romy Suwahyu (Journal Public Health and Clinical Science, 2026)
Chronic conditions such as chronic obstructive pulmonary disease, heart failure, and cancer can disrupt daily activities and reduce quality of life. One frequently used non-pharmacological intervention is the handheld fan, which is a handheld fan directed at the face to provide airflow that can help reduce the perception of shortness of breath through trigeminal receptor stimulation. Purpose: This journal review was conducted to determine the extent to which a handheld fan is effective in reducing complaints of shortness of breath in various clinical conditions through a scoping review approach. Methods: This review was conducted by searching and reviewing research articles from Google Scholar, PubMed, and national journals in the period 2021–2025 using the PICO framework, which includes a patient population with shortness of breath, handheld fan intervention, a control group comparison or no comparison, and outcomes in the form of a reduction in dyspnea levels. A total of 10 articles met the inclusion criteria and were analyzed descriptively. Results: The use of a hand-held fan for 5–10 minutes at a distance of 15–30 cm was consistently effective, demonstrating a reduction in shortness of breath in patients with chronic disease. No adverse effects were observed in all studies. Therefore, a handheld fan is considered safe, easy to implement, and potentially helpful in managing dyspnea.